Bioenergetic Processes of Cyanobacteria From Evolutionary Singularity to Ecological Diversity - Peschek, Guenter A.; Obinger, Christian; Renger, Gernot; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This publication is unique among a number of books on cyanobacteria because it focuses on the bioenergetics of these widespread organisms which are the evolutionary prerequisite for the development of all higher forms of life on our "blue" planet. The book primarily addresses questions of energy conversion by the fundamental bioenergetic processes: (oxygenic) photosynthesis, (aerobic) respiration, and (anaerobic) fermentation which uniquely occur together in these prokaryotic cells. Thermophilic cyanobacteria offer the most suitable material for high resolution structure analyses of Photosystem I and II and other electron transport complexes by X-ray crystallography (for example, at present the structure of Photosystem II at atomic resolution is only known for these organisms). These achievements during the last decade represent a milestone in our understanding of the complexes which are crucial for solar energy exploitation through photosynthetic water splitting. The present work represents an ambitious attempt to achieve the goal of a synoptic state-of-the-art picture by casting together the mosaics of detailed knowledge described by leading experts in the field. It contains 24 chapters written by 35 authors from Europe, USA, India and Japan. The book is aimed at reaching a broad audience ranging from students to experienced scientists. The editors wish all readers a pleasant and stimulating journey through the fascinating (3z(Bworld(3y (Bof the bioenergetics of cyanobacteria and sincerely hope that this book will not only be of great value for the experts but also entice young people into this exciting research area with the aim to address successfully the challenging problems of high relevance that are still waiting for a satisfactory answer.s
Keywords: Life sciences; Biochemistry; Cytology; Ecology; Evolution (Biology).; Life Sciences; Life Sciences, general; Plant Biochemistry; Cell Biology; Ecology; Evolutionary Biology; Cell Physiology